2020
DOI: 10.14202/vetworld.2020.1654-1660
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the sex, age, and breed of farmed rabbits and the choice of management system on the extensity and intensity of Eimeria infection

Abstract: Background and Aim: The most common causes of loss and diarrhea in rabbit farming are nutritional errors and coccidiosis. The infection can spread rapidly throughout a breeding area, reducing the rabbit population, and causing heavy losses. The aim of the study was to determine the influence of the system of animal management on the extensity and intensity of infection by Eimeria of farmed rabbits, together with the effect of the sex, age, and breed of the rabbits themselves. Materials and Methods: The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…In contrast, suckling kittens during their first 20 days of age are rarely infected with coccidia [82]. One study found a higher intensity and extensity of coccidia invasion in rabbits kept in groups, like the rabbits in the present case, compared to rabbits housed individually [83]. Coccidiosis outbreaks have also been associated with an increase in Escherichia coli [84], and other intestinal bacterial infections [85] in rabbits.…”
Section: Discussionmentioning
confidence: 42%
“…In contrast, suckling kittens during their first 20 days of age are rarely infected with coccidia [82]. One study found a higher intensity and extensity of coccidia invasion in rabbits kept in groups, like the rabbits in the present case, compared to rabbits housed individually [83]. Coccidiosis outbreaks have also been associated with an increase in Escherichia coli [84], and other intestinal bacterial infections [85] in rabbits.…”
Section: Discussionmentioning
confidence: 42%
“…At the end of the experimental period (112-day old rabbits), rabbits of the group E showed significantly lower OPG count as compared to those in the C group (P <0.01); this decrease can be attributed to the anticoccidial effect of medicinal plant Artemisia vulgaris included in the experimental pelleted diet. Pilarczyk et al (2020) reported age effect of rabbits on the Eimeria infection. In generally it can be stated that rabbit at the age of 1 to 3 months are most susceptible to the disease (Pakandl et Hlásková, 2007;Papeschi et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the presence of oocysts in fecal samples does not confirm the presence of clinical disease. It has been reported that rabbits with high-intensity infection showed no clinical symptoms of coccidiosis (Pilarczyk et al, 2020). The induction of symptoms may depend on the virulence and pathogenicity of the infecting Eimeria spp.…”
Section: Laboratory Diagnosismentioning
confidence: 99%
“…Prevention and control of coccidiosis in rabbits are achieved through careful management, enhancing rabbits' immunity, vaccination, and using synthetic anticoccidial drugs. Housing in large, dry, sunny, and disinfected rooms is very essential to fight coccidial infection (Pilarczyk et al, 2020). Although synthetic anticoccidials were effective, their hazardous use in the field resulted in some drawbacks.…”
Section: Introductionmentioning
confidence: 99%